Charles Mackerras - Simeone, Nigel 1956-; Tyrrell, John 1942- (The Boydell Press, 2015)
By the time of his death in 2010 at the age of 84, Sir Charles Mackerras had achieved widespread recognition, recorded extensively and developed into a conductor of major international significance. In addition to areas in which he already had forged a distinctive profile (Janacek, Mozart, Handel, Sullivan) he revisited - and rethought - much of the standard repertoire. The last thirty years were particularly momentous in the coming to fruition of so many cherished projects: not only the Janacek operas but the Gilbert and Sullivan series, the Mozart operas, the two Beethoven cycles, other projects with the Scottish Chamber Orchestra (Schumann and Brahms at Edinburgh; the outstanding late Mozart) and at the Royal Opera House and the Met. Unspoilt by fame, and undeterred by personal tragedies and increasing physical frailty, he remained productive and inventive: for him music-making, whether with world-class singers and orchestras or with students, was a kind of joyous oxygen that kept him going right to the end. A detailed account of his life is complemented by contributions from performers and scholars who worked closely with Mackerras, as well as interviews with his family. The book is richly illustrated with photographs and documents, and includes a comprehensive discography along with listings of many of his concert and opera performances. While Sir Charles's whole life is considered, emphasis is given to his final quarter century, a period in which so many important projects were realized. This book celebrates and epitomizes an exceptional life.